Chemistry of Indoles : New Reactivities of Indole Nucleus and Its Synthetic Application - MURAKAMI, Yasuoki (YAKUGAKU ZASSHI, 1999)
This review summarizes our studies on the development of new reactivities of the indole nucleus and on its application for the synthesis. These studies involve the following five main subjects : 1) The Vilsmeier-Haack reaction was applied to 1, 2, 3, 4-tetrahydrocarbazole and its N-alkyl compounds. The conditions and the mechanisms of the formation of three kinds of products obtained from the latter compound were clarified, and among the three products, 1, 9-dimethylcarbazole-3-aldehyde was found to be useful for the syntheses of olivacine and ellipticine. 2) The Fischer indole synthesis of various 2-substituted phenylhydrazones was examined in detail and it was found that the Fischer indole synthesis of 2-sulfonyloxyphenylhydrazones served a new and convenient method for the synthesis of 7-oxygenated indoles. This reaction was applied to the synthesis of eudistomidin-A. 3) The reactivities of ethyl indole-2-carboxylate for acylation and bromination were also studied, and the use of this compound as a starting material for the synthesis of 4-methoxy-β-carbolines was successfully investigated. 4) Acylation of ethyl pyrrole-2-carboxylate was concisely studied and this reaction was applied to the syntheses of benzene ring-substituted indoles and benz[f]indoles involving eupolauramine. 5) Two kinds of method for the debenzylation of N-benzylindoles were developed using either AlCl3-benzene or methyl lithium, and they are complementary with each other.